Comprehensive taxonomic, faunistic, biological, and geographic inventory and analysis of the Sciomyzidae (Diptera: Acalyptratae) of the Delmarva region and nearby states in eastern North America - Murphy, William L.; Mathis, Wayne N.; Knutson, Lloyd V. (Zootaxa, 2018)
Genera and species of Sciomyzidae known from the Delmarva region (Delaware, the District of Columbia, Maryland, Virginia, and West Virginia) and nearby states are reviewed taxonomically, faunistically, biologically, and geographically. Although restricted to the taxa in that area, this work amounts to a revision of the sciomyzid fauna of that portion of the Nearctic region. Treated are 91 species in 19 genera, i.e. 46% of the 199 species and all but four of the 23 genera of Sciomyzidae known from the Nearctic Region. Included are 67 species in 16 genera from Delmarva and 24 other species in 10 genera from nearby states. Euthycera flavescens (Loew) is resurrected; Renocera cressoni Mathis and Knutson sp. nov. is described from eastern North America; R. amanda Cresson is given new status as a junior synonym of R. longipes (Loew); and Chaetomacera brevis Cresson, R. cyathiformis Melander, R. pacifica Curran, and R. bergi Steyskal are given new status as junior synonyms of R. striata (Meigen). Newly diagnosed are taxonomic categories ranging from family to species level, including the first diagnoses of abdomens of females of many species, where known. Provided for each genus and species are annotated taxonomic/nomenclatorial catalogs of all North American references to all species, with generic combinations noted, with previously unrecorded synonymies as well as North American literature references, illustrations, and information on natural history and morphology of immature stages. Results of cross-mating studies of Dictya are reported and discussed. Provided are label data from examined specimens, lists of Canadian provinces and U.S. states from which reviewed species have been recorded, and detailed maps of geographical distribution of species in Delmarva, with references to previously published maps.